PERAN GURU DALAM MENGINTERNALISASIKAN NILAI- NILAI MORAL SOSIAL PEMBELAJARAN IPS SMPN 22 PONTIANAK - Norsita Norsita; Sulistyarini Sulistyarini; Izhar Salim (Universitas Tanjungpura, 2021)
AbstractThis study aims to explain the teacher's role in internalizing social moral values insocial studies learning in class VII A SMPN 22 Pontianak